Whole-brain morphometric studies in alcohol addicts by voxel-based morphometry - Li, Jinfeng (Ann Transl Med, 2019)
BACKGROUND: To investigate the morphological changes of the whole-brain in patients with alcohol addiction using voxel-based morphometry (VBM). METHODS: Twenty alcohol addiction individuals and 20 healthy control volunteers, matched in gender, age, handedness and education, were enrolled as the alcohol addiction group and control group, respectively, from June 2017 to February 2018. The two groups underwent magnetic resonance imaging (MRI) scans of the whole-brain using a 3.0T MRI system, and the MRI images were analyzed by VBM. Total brain volume analysis was performed to observe the changes of local brain volume. Independent samples t-test was used for comparison of whole-brain volumes between the two groups. RESULTS: Gray matter volume (GMV) was significantly more reduced in the left middle frontal gyrus, left superior frontal gyrus, left precuneate gyrus, left gyrus rectus, right medial superior frontal gyrus, and right orbital gyrus in patients with alcohol addiction than in healthy controls. White matter volume (WMV) in the bilateral superior frontal gyrus was also significantly more reduced in patients with alcohol addiction than in healthy controls. Whole-brain VBM results showed that white matter and brain parenchyma volumes (BPVs) were significantly smaller in patients with alcohol addiction than in healthy controls (both P<0.05). There was no significant difference in GMV between patients with alcohol addiction and healthy controls (P>0.05). CONCLUSIONS: There are dominant areas of brain atrophy in patients with alcohol addiction. The VBM has a potential application value in detecting subtle brain atrophy in patients with alcohol addiction and providing an imaging basis in the diagnosis of alcohol addiction.